NUT Carcinoma of the Lung：A Case report and Literature Analysis - Zhao, Rongshuang; Hua, Ze; Hu, Xiaodong; Zhang, Qi; Zhang, Jin; Wang, Jian (Frontiers in Oncology, 2022)
NUT carcinoma is a rare, highly aggressive cancer which feature as the rearrangement of the nuclear protein in testis (NUT) gene on chromosome 15q14, and its pathogenesis and treatment is not yet clear. In this case, we report a 40-year-old male patient who was diagnosed as primary pulmonary NUT carcinoma in The Second Affiliated Hospital of Zhengzhou University. A tumor was found at the right hilus pulmonis when his physical examination with chest pain for half a month. Histopathology confirmed by fluorescence in situ hybridization technique for the NUT carcinoma. After chemotherapy, radiotherapy, immunotherapy and targeted therapy were given, the patient died. The overall survival time was 4.7 months. Combined with the existing literature, we retrospective report the clinical and pathological characteristics, and treatment strategies of the rare lung NUT carcinoma.